A comprehensive data-driven study of electrical power grid and its implications for the design, performance, and operational requirements of adiabatic compressed air energy storage systems. (1st January 2020) - Rouindej, Kamyar; Samadani, Ehsan; Fraser, Roydon A.
Highlights: A data driven approach is introduced for designing A-CAES systems. High fidelity data of Ontario power system is analyzed to identify grid profiles. A-CAES performance requirements are simulated for multiple operating scenarios. The system sizing is found to be highly sensitive to desired coverage rates. Designing an A-CAES for maximum capacity can result in severe under-utilization. Abstract: As the next generation of compressed air energy storage systems are being developed and the technology is gaining momentum, designing the right system is essential for its successful adaptation in the electricity market. This research studies the impact of performance requirements on the design and operation of any potential adiabatic compressed air energy storage system, using one full year worth of real operating data of the Ontario grid for analysis. The objective is to introduce a new approach to designing compressed air energy storage systems based on specific grid requirements. The adiabatic compressed air energy storage system thermo-mechanical requirements under real operating conditions are identified using a model-based approach. It is shown that using an adiabatic compressed air energy storage system with one-tenth of the size commonly assumed in the literature, will satisfy the Ontario grid requirements. Such a system will require charge and discharge durations of less than two hours. In addition to understanding sizing and performance requirements, this analytical approach provides a valuable insight into long-term trends required for optimum operational planning and scheduling.